2022
DOI: 10.3389/fmicb.2022.891188
|View full text |Cite
|
Sign up to set email alerts
|

Seed-Borne Erwinia persicina Affects the Growth and Physiology of Alfalfa (Medicago sativa L.)

Abstract: Seed-borne Erwinia persicina can be transmitted globally via alfalfa (Medicago sativa L.) seed trade, but there is limited information about the impact of this plant-pathogenic bacterium on alfalfa plants. In this study, strain Cp2, isolated from alfalfa seeds, was confirmed by whole-genome sequencing to belong to E. persicina. Subsequently, the effects of Cp2 on alfalfa growth and physiology were evaluated by constructing a rhizosphere infection model. Strain Cp2 had a strong inhibitory effect on the elongati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…Many Pantoea species are phytopathogenic bacteria with a wide host range; however, there are no reports of Pantoea causing alfalfa disease [28]. In this work, we characterized the strain CQ10 as a novel pathogen of alfalfa bacterial leaf blight, which enriches the list containing only Xanthomonas alfalfae and Erwinia persicina as pathogens of alfalfa bacterial leaf blight [3,6]. Further genomic analysis revealed that strain CQ10 possesses diverse virulence attributes, which may support a broad pathogenic potential, similarly to its close relative P. agglomerans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many Pantoea species are phytopathogenic bacteria with a wide host range; however, there are no reports of Pantoea causing alfalfa disease [28]. In this work, we characterized the strain CQ10 as a novel pathogen of alfalfa bacterial leaf blight, which enriches the list containing only Xanthomonas alfalfae and Erwinia persicina as pathogens of alfalfa bacterial leaf blight [3,6]. Further genomic analysis revealed that strain CQ10 possesses diverse virulence attributes, which may support a broad pathogenic potential, similarly to its close relative P. agglomerans.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, alfalfa seeds were washed five times with sterile distilled water. The growth bottles were used for alfalfa plant inoculation experiments [6]. Briefly, CQ10 inoculum suspension (200 mL/bottle) was added to the growth bottles.…”
Section: Alfalfa Plant Inoculation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, ANI values <95–96% or dDDH values <70% indicate that the strain does not belong to any known species. A heatmap based on ANI values was generated using TBtools software ( Yao et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%